UPAYA PEMANTAPAN KETAHANAN PANGAN NASIONAL MELALUI REVITALISASI DI SEKTOR PERTANIAN DALAM RANGKA MENGURANGI FENOMENA ALIH FUNGSI LAHAN PERTANIAN MENJADI KAWASAN INDUSTRI - Siti Syuhada (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
The problem of malnutrition was the inability of the community to satisfy their need especially food. Moreover, the community that was in the rural area, they commonly as the farmer. The farmers in Indonesia suppose increase their productivity, but farming which oriented to the market and the improvement of the agricultural system that was based on agricultural technology, so itcould increase their income. If the community could not increase the income, then the role of the government in order to reduce poverty and the unemployment is to increase the activity by revitalized the sector of agriculture, so it will be able to reduce the unemployment. Because, most Indonesian inhabitants are the farmer and it match with geographical condition in Indonesia.Overseas, many countries that majority of their community as the farmer and could increase their income that was relied on from the sector of agriculture. But the problem of the land change in function could resulting from the policy that was not directed become the phenomenon for the farmer to maintain his life from the sector of agriculture. The farmer is a job that almost some Indonesian communities relied on his life from this sector. Necessarily this sector must be maintained with renovation of agricultural technology. Overseas, their community relied on their life from the sector of agriculture that caused their country could develop. If the matter continued to be developed with the modern agricultural system, then the industrial group will not dare to shift the function of the agricultural land to the industrial region. But the policy of this change in function sometimes the farmer's group always treated as a stepchild by the government compared with the group indistri resulting from interest politics that happened.If the rice cultivation land already changed, then it will influence the income of the farmer and had a bad impact on national food endurance. Food endurance not only means of the availability of food, but also the capacity to buy food and not the occurrence of the dependence with any side. National food endurance depends on the production of the rice that keeps it increase and not causes the instability of food. The destiny of the rice farmer in Indonesia also will affect many social problems, they will become the unemployment and will become the social problem and protracted economics.Keywords:  rice cultivation, farmers, economy, agriculture